Lobbying and negotiation practices as messages and forms of political communication in the Indonesian government - Teguh nurjaman; Harmonis, Harmonis (Jurnal Info Sains : Informatika dan Sains, 2024)
The practice of lobbying and negotiation by government officials has become commonplace in various countries in the world, but in reality the practice of lobbying and negotiation is often seen as the worst thing involving conflict in politics. In fact, lobbying or interest representation is closely related to politicians or administrative authorities who usually target certain groups. Meanwhile, negotiation is defined as an approach to managing conflict in interpersonal or group settings, which is intended to reduce differences between incompatibilities and end with an agreement. The researcher used descriptive analysis as a research method, using a qualitative approach, and the results explained that, in politics, lobbying and negotiation are needed to carry out negotiations to reach an agreement between the negotiators. To reach an agreement and win goals in negotiations, of course political communicators need a strategy, which canbe done through a distributive approach. In political communication, political lobbying and negotiation rhetoric should be carried out face to face and door to door, because both require a more personal space so that the goal of persuasion is more possible so that dialogue and compromise can occur. Lobbying and negotiations carried out by political communicators target stakeholders. For this reason, the political communicator's skills in interacting with the general public are an important focus, because the lobbying and negotiation process is considered complete if the desired agreement has been achieved.